Features of software for a high-power infrared free electron laser - Kondakov, A.A.; Kurkin, G.Ya.; Oreshkov, A.D.; Salikova, T.V.; Scheglov, M.A.; Tribendis, A.G.; Vinokurov, N.A. (Вопросы атомной науки и техники, 2001)
The control system of the high power infrared FEL is the classical two-level distributed control system built on a basis of EPICS. This paper describes the software features of a control system and discuss the architecture ported variant of EPICS which is used for automation of the FEL complex.